Extended Abstracts of the 2020 CHI Conference on Human Factors in Computing Systems 2020
DOI: 10.1145/3334480.3383144
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of FoodFab: Creating Food Perceptual Illusions using Food 3D Printing

Abstract: Food 3D printing enables the creation of customized food structures based on a person's individual needs. In this paper, we demonstrate the use of food 3D printing to create perceptual illusions for controlling the level of perceived satiety given a defined amount of calories. We present FoodFab, a system that allows users to control their food intake through modifying a food's internal structure via two 3D printing parameters: infill pattern and infill density. In two experiments with a total of 30 participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
5
0
1
Order By: Relevance
“…Only very few studies (Chow et al, 2021;Fahmy et al, 2021;Kistler, Pridal, Bourcet, & Denkel, 2021;Mantihal et al, 2019;Punpongsanon et al, 2020;Zhu, Ribberink, De Wit, Schutyser, & Stieger, 2020) investigated how structural modifications created by 3D printing impact consumer and sensory perception of foods. These studies explored sensory and oral behavioral responses (sweetness perception, texture preference and mastication behaviour) rather than texture perception of 3D printed foods.…”
Section: Introductionmentioning
confidence: 99%
“…Only very few studies (Chow et al, 2021;Fahmy et al, 2021;Kistler, Pridal, Bourcet, & Denkel, 2021;Mantihal et al, 2019;Punpongsanon et al, 2020;Zhu, Ribberink, De Wit, Schutyser, & Stieger, 2020) investigated how structural modifications created by 3D printing impact consumer and sensory perception of foods. These studies explored sensory and oral behavioral responses (sweetness perception, texture preference and mastication behaviour) rather than texture perception of 3D printed foods.…”
Section: Introductionmentioning
confidence: 99%
“…They successfully created confectionary products with enhanced sweetness while maintaining the same sugar content (Kistler et al, 2021). Variation in porosity of 3D printed cookies influenced consumers' chewing time, which might potentially affect satiation (Punpongsanon et al, 2020). These studies demonstrated that 3D printing can be used to create healthier foods by either creating an inhomogeneous distribution of food components or by creating porous structures.…”
Section: Customization Of Printed Structures To Modify Texture Percep...mentioning
confidence: 96%
“…3D printing can also impact consumer and sensory perception of foods and its effect depends on the formulation and printing designs. A few recent studies explored sweetness perception (Khemacheevakul et al, 2021;Kistler et al, 2021), saltiness perception (Fahmy et al, 2021), texture preference (Mantihal et al, 2019) and mastication behaviour (Punpongsanon et al, 2020) of 3D printed foods. As an example, Kistler et al (2021) used 3D printing to prepare confectionery products with an inhomogeneous spatial distribution of sucrose.…”
Section: Powder Bed Printingmentioning
confidence: 99%
See 2 more Smart Citations